Notes on world Agromyzidae, with the description of 16 new species (Diptera: Agromyzidae). - Spencer, Kenneth Angus (Contributions to Entomology = Beiträge zur Entomologie, 1977)
Sixteen new species from North and South America, West and South Africa and from India and Pakistan are discribed; two new synonymies are established and a new subgenus in Amauromyza is proposed. In addition, holotypes of 4 species are clarified with drawings of the male genitalia and notes with drawing are given on 5 further species. Five species collected in Nigeria are recorded. Nomenclatural Acts nigrisquama Malloch, 1914 (Agromyza), syn. n. of Melanagromyza provecta (de Meijere, 1910) virginiensis Spencer, 1977 (Agromyza), spec. n. Catalpomyza Spencer, 1977 (Amauromyza), sgen. n. pleuralis (Malloch, 1914) (Amauromyza (Catalpomyza)), comb. n. hitherto Agromyza pleuralis trispinata Spencer, 1977 (Cerodontha (Cerodontha)), spec. n. trispinella Spencer, 1977 (Cerodontha (Cerodontha)), spec. n. trispinosa Spencer, 1977 (Cerodontha (Cerodontha)), spec. n. atrissima Spencer, 1977 (Cerodontha (Icteromyza)), spec. n. stuckenbergiella Spencer, 1977 (Cerodontha (Icteromyza)), spec. n. abutilonicaulis Spencer, 1977 (Hexomyza), spec. nov. antiquaria Spencer, 1977 (Liriomyza), spec. n. xanthocera (Czerny, 1910) (Liriomyza), comb. n. hitherto Agromyza xanthocera obscura Spencer, 1977 (Melanagromyza), spec. n. principensis Spencer, 1977 (Melanagromyza), spec. n. tamsi Spencer, 1977 (Melanagromyza), spec. n. tunisiensis Spencer, 1977 (Ophiomyia), spec. n. ecuadorensis Spencer, 1977 (Phytobia), spec. n. nigeriensis Spencer, 1977 (Phytobia), spec. n. peruensis Spencer, 1977 (Phytobia), spec. n. cisti Spencer, 1960 (Phytobia (Praspedomyza)), syn. n. of Liriomyza xanthocera (Czerny, 1910) mexicana Spencer, 1977 (Phytoliriomyza), spec. n.